Influence of Workload, Competence and Work Environment on Employee Performance at the Astra Motor Gajahmada Semarang Dealer Workshop - Nurbiyanti; Inayah; Mona Inayah Pratiwi (Admisi dan Bisnis, 2026)
This research seeks to investigate the impact of Workload, Competence, and Work Environment on employee performance at the Astra Motor Gajahmada Semarang Workshop. The research applied a quantitative approach with a non-probability sampling technique. Responses were collected via questionnaires distributed to 30 respondents and subsequently xamined through multiple linear regression using SPSS version 25. The results indicate that Competence has a significant impact on employee performance, with a t-value of 2.123 and a significance level of 0.043 (< 0.05). In contrast, Workload and Work Environment do not show a significant effect on employee performance, with significance values of 0.173 and 0.382 (> 0.05), respectively. The Adjusted R² value of 0.454 shows that 45.4% The fluctuations in employee performance are influenced by these three independent variables, while the residual 54.6% is influenced by other factors outside the scope of this study. Therefore, Competence is the most influential factor in improving employee performance at the workshop.